THE GLORY THAT IS ROME. - Perrottet, Tony; T. P. (Smithsonian, 2005)
Focuses on the renovation of ancient sites in Rome, Italy. Domination of the Campidoglio, or Capitoline Hill, with the renovated Capitoline Museums--the oldest public museums in the world; Details of three different rebirths of archaeological interest in Rome, the first in the 1870s when King Victor Emmanuel II ordered the Colosseum and Forum cleared of rubble, the second when Mussolini exposed the port of Ostia, and the latest in the 1990s; Influence of the advent of Grand Jubilee millennium festivities in funneling money into renovations and long-dormant projects. INSET: HBO'S ROME.